A hunger for aesthetics : enacting the demands of art - Kelly, Michael, 1953- (Columbia themes in philosophy, social criticism, and the arts., 2012)
For decades, aesthetics has been subjected to a variety of critiques, often concerning its treatment of beauty or the autonomy of art. Collectively, these complaints have generated an anti-aesthetic stance now prevalent in the contemporary art world. Yet if we examine the motivations for these critiques, Michael Kelly argues, we find theorists and artists hungering for a new kind of aesthetics, one better calibrated to contemporary art and its moral and political demands. Following an analysis of the work of Stanley Cavell, Arthur Danto, Umberto Eco, Susan Sontag, and other philoso.